Isolation and Purification of Endotoxin by Hydrolytic Enzymes - Lehrer, Samuel (1972)
Various commercial hydrolases were used in an attempt to degrade the endotoxic lipopolysaccharide macromolecule. Some inert components, such as peptides and nucleic acids, could be removed from endotoxin preparations. As a result, endotoxic activity, measured by pyrogenicity, Shwartzman reaction, and mouse lethality, was increased. The remarkable resistance of endotoxin to hydrolases led to the use of such enzymes for the liberation and purification of endotoxin from whole bacterial cells.